A homozygous genome‐edited Sept2‐EGFP fibroblast cell line. Issue 1 (19th April 2019) - Banko, Monika; Mucha‐Kruczynska, Iwona; Weise, Christoph; Heyd, Florian; Ewers, Helge
Abstract: Septins are a conserved, essential family of GTPases that interact with actin, microtubules, and membranes and form scaffolds and diffusion barriers in cells. Several of the 13 known mammalian septins assemble into nonpolar, multimeric complexes that can further polymerize into filamentous structures. While some GFP‐coupled septins have been described, overexpression of GFP‐tagged septins often leads to artifacts in localization and function. To overcome this ubiquitous problem, we have here generated a genome‐edited rat fibroblast cell line expressing Septin 2 (Sept2) coupled to enhanced green fluorescent protein (EGFP) from both chromosomal loci. We characterize these cells by genomic polymerase chain reaction (PCR) for genomic integration, by western blot and reverse transcriptase‐PCR for expression, by immunofluorescence and immunoprecipitation for the colocalization of septins with one another and cellular structures and for complex formation of different septins. By live cell imaging, proliferation and migration assays we investigate proper function of septins in these cells. We find that EGFP is incorporated into both chromosomal loci and only EGFP‐coupled Sept2 is expressed in homozygous cells. We find that endogenous Sept2‐EGFP exhibits expression levels, localization and incorporation into cellular septin complexes similar to the wt in these cells. The expression level of other septins is not perturbed and cell division and cell migration proceed normally. We expect our cell line to be a useful tool for the cell biology of septins, especially for quantitative biology.